EINE BETRACHTUNG DER DARGESTELLTEN LEHRMETHODEN JESU IM MATTHÄUSEVANGELIUM AUS DER PERSPEKTIVE DER METHODEN DER ERLEBNISPÄDAGOGIK - M. Hagel (Acta Theologica)
The Gospel of Matthew is a narrative in its literary form. Jesus, the meaning of his life, and his divine mission constitute the central message of the Gospel of Matthew. The narrative exegesis of Matthew is especially suited to the analysis and literary characterisation of the teaching methods of Jesus. Essential passages of the Gospel of Matthew which reveal the teaching methods of Jesus and learning process of the disciples are first identified, then narrowed down, and finally analysed in their narrative. The results of Jesus’ teaching methods are subsequently compared with contemporary experiential education. The presentation and characteristic of the teaching methods of Jesus are compiled in this manner in order to discover any non-obvious presentations of Jesus’ teaching methods.